ChemInform Abstract: Catalytic, Green and Regioselective Friedel‐Crafts Acylation of Simple Aromatics and Heterocycles Over Zeolites. Issue 36 (September 2015) - El‐Hiti, Gamal A.; Smith, Keith; Hegazy, Amany S.
Abstract Review: 152 refs.